Experimental characterisation of near field backscatter from thin resistively loaded FSS absorbers. Issue 24 (1st November 2017) - McGuigan, N.; Conway, G.; Cahill, R.; Zelenchuk, D.; Zabri, S.
Abstract : Experimental results are employed to show that a thin metal backed resistively loaded frequency selective surface (FSS) exhibits significant radar backscatter suppression when the structure is illuminated by an antenna placed in close proximity to the periodic array. This is investigated in the range 9–11 GHz by measuring the shift in the resonant frequency of an impedance matched (| S 11 | ∼15 dB at 10.22 GHz) microstrip patch which is placed in five different positions ranging from λ /30 to λ /5 distance above the surface of the FSS. Detuning of the antenna by signals reflected from the absorber surface is shown to be much less significant than the upward frequency shift in the measured | S 11 | for a metal plate and tissue phantom, therefore this technology could be used to enhance the performance of on‐body wireless sensors.